Konsentrasi Asam Sitrat terhadap Mutu Sari Buah Mangga Indramayu - Kiayi, Geralvi S (Gorontalo Agriculture Technology Journal, 2018)
Mango (Mangifera Indica L.) cengkir known as the mango from indramayu, so often referred to as the mango indramayu or dermayu. this study aims to know the fruit juice mango indramayu instant and know the concentration of citric acid to quality organoleptic sari mango indramayu instant. step of kerjaa of this study include the preparation of materials and equipment, weighing, cutting, blanching, destruction, filtering, the addition of citric acid and egg whites, drying, in a blender, the addition of sugar, packaging. this study was conducted in the laboratory faculty of agriculture University gorontalo and laboratory polyteknik gorontalo. research methods do is the design of randomized complete with three treatment (0,7%, 0,8%, 1%) and the three times Deuteronomy so that the number of observations is 3. the analysis of the concentration of citric acid include the analysis of water content, vitamin C., and test organoleptic. the results showed that citric acid as much as 1% make water content high ie 2,07 on treatment a3, citric acid in vitamin C. the 5,74 a1. and at the test organoleptic panelists terms of color, sense, the smell like treatment on a1 ie 0,7% citric acid.Keywords : citric acid, mango, vitamin C, organoleptik